Peripheral immune responses to filoviruses in a reservoir versus spillover hosts reveal transcriptional correlates of disease - Guito, Jonathan C.; Arnold, Catherine E.; Schuh, Amy J.; Amman, Brian R.; Sealy, Tara K.; Spengler, Jessica R.; Harmon, Jessica R.; Coleman-McCray, Joann D.; Sanchez-Lockhart, Mariano; Palacios, Gustavo F.; Towner, Jonathan S.; Prescott, Joseph B. (Frontiers in Immunology, 2024)
Several filoviruses, including Marburg virus (MARV), cause severe disease in humans and nonhuman primates (NHPs). However, the Egyptian rousette bat (ERB, Rousettus aegyptiacus), the only known MARV reservoir, shows no overt illness upon natural or experimental infection, which, like other bat hosts of zoonoses, is due to well-adapted, likely species-specific immune features. Despite advances in understanding reservoir immune responses to filoviruses, ERB peripheral blood responses to MARV and how they compare to those of diseased filovirus-infected spillover hosts remain ill-defined. We thus conducted a longitudinal analysis of ERB blood gene responses during acute MARV infection. These data were then contrasted with a compilation of published primate blood response studies to elucidate gene correlates of filovirus protection versus disease. Our work expands on previous findings in MARVinfected ERBs by supporting both host resistance and disease tolerance mechanisms, offers insight into the peripheral immunocellular repertoire during infection, and provides the most direct known cross-examination of the response genes, pathways and activities prevalently associated with differences in filovirus pathogenesis and pathogenicity between reservoir and spillover hosts.